Effect of Government Expenditure on GDP in the Turkish Economy - E. Simsek; M. Orhan; F. Macit (International Econometric Review (IER), 2017)
The objective of this article is to investigate the effect of government expenditure on GDP in Turkey from 2000Q1-2015Q4 by the superexogeneity test. As a consequence of satisfying both conditions of weak exogeneity and structural invariance, government expenditure is super exogenous to GDP which implies that the policy regime shift for the period of the Global Financial Crisis in Turkey did not cause structural variance in government expenditure. Indeed, the Lucas Critique which indicates that policy regime shifts cause structural breaks, appears to be refuted
Keywords: E52; H5; C22; C52; 330; Lucas Critique; Government Expenditure; Superexogeneity Test